Factors Associated with Age at Diagnosis of Autism Spectrum Disorder in Pediatric Patients at Sawanpracharak Hospital, Thailand - Wannapaschaiyong, Prakasit; Teekavanich, Sineenat (Siriraj Medical Journal, 2023)
Objective: This study aimed to determine the average age at diagnosis and the characteristics associated with the age of children at the diagnosis of autism spectrum disorder (ASD) at Sawanpracharak Hospital. Materials and Methods: A retrospective cross-sectional study was conducted from May 2023 to July 2023. Data were collected from the medical patient files of all children diagnosed with ASD between 2020 to 2022. Descriptive analysis was used to examine the characteristics of the children and their caregivers, and the children’s age at diagnosis. Factors associated with the age at diagnosis were assessed by chi-square test analysis. Results: In total, 100 patient records with complete information were collected. The average age at the diagnosis of ASD was 4.57± 1.61 years old, with 60% of the patients diagnosed after four years of age. Social communication deficit symptoms, including non-response to name and lack of pointing out objects of interest, were significantly associated with an early ASD diagnosis (p-value = 0.023 and 0.002, respectively). Being a firstborn child and the presence of delayed development were found to delay the diagnosis of ASD meaning it occurred at a later age (p-value = 0.002 and 0.019, respectively). However, sex, the caregiver’s education, and socioeconomic status were not related to the age at diagnosis. Conclusion: Most children with ASD who received treatment at Sawanpracharak Hospital were diagnosed late. Being a firstborn child, poor response to name being called, lack of pointing out objects of interest, and delayed development were related to the age of the children at ASD diagnosis. Differences in diagnostic age based on sociodemographic and clinical characteristics indicate the need for coordinated measures for the early detection of ASD.